Fiction Unbound : Bernardine Evaristo. - Toplu, Sebnem (Cambridge Scholars Pub., 2011)
This book covers all Bernardine Evaristo's major works: Lara (1997) and Lara (2009), The Emperor's Babe, Soul Tourists, Blonde Roots and Hello Mum. Each chapter focuses on a particular novel, combining a close analysis of the author's technique with a penetrating understanding of Evaristo's basic themes underlying all her work. This monograph exposes that Evaristo is not simply interested in "multicultural" issues; to label them as such is to overlook her achievement as a novelist. It shows i ...